Cycle Voltametry Performance of Nitrogen-Doped Reduced Graphene Oxide Derived from Oil Palm Empty Fruit Bunch for Sodium-Ion Batteries - Sihombing, Gunawan; Yamin, Octo Muhammad; Noer, Zikri; Lubis, Hariyati; Agus, Muhammad Abduh Akram; Idamayanti, Dewi (Journal of Technomaterial Physics, 2025)
This study investigates the electrochemical performance of nitrogen-doped reduced graphene oxide (NRGO) derived from oil palm empty fruit bunches as an anode material for sodium-ion batteries (SIB). The aim is to evaluate the potential of NRGO to enhance sodium-ion storage through cyclic voltammetry (CV) analysis. The NRGO was synthesized using a modified Hummers method followed by nitrogen doping through thermal treatment under an ammonia atmosphere. Cyclic voltammetry measurements were conducted at scan rates of 0.2 mV/s, 1 mV/s, and 10 mV/s to analyze the redox behavior and charge storage capacity. At a low scan rate of 0.2 mV/s, the current response was minimal, indicating limited sodium-ion intercalation. At 1 mV/s, the current increased, suggesting enhanced ionic mobility, though no distinct redox peaks were observed, implying a primarily capacitive mechanism. At the highest scan rate of 10 mV/s, the current response increased further, but the absence of clear redox peaks persisted, indicating limited faradaic reactions. The initial CV cycles showed a higher current due to the formation of a solid electrolyte interphase (SEI) layer and structural rearrangements, which stabilized in subsequent cycles. The overall charge storage mechanism appears to be dominated by double-layer capacitance rather than faradaic processes. These findings suggest that NRGO derived from oil palm empty fruit bunches exhibits moderate electrochemical performance as a SIB anode material. While the material demonstrates promising charge storage capabilities, further optimization is required to enhance redox activity. Future research should focus on improving synthesis conditions, such as increasing nitrogen doping levels and enhancing surface area, to achieve better electrochemical performance and make NRGO a viable candidate for sodium-ion battery applications.